The Routledge Companion to Critical Approaches to Contemporary Architecture - Chattopadhyay, Swati 1962-; White, Jeremy (Routledge companions, 2020)
The Routledge Companion to Critical Approaches to Contemporary Architecture convenes a wide array of critical voices from architecture, art history, urbanism, geography, anthropology, media and performance studies, computer science, bio-engineering, environmental studies, and sociology that help us understand the meaning and significance of global architecture of the twenty-first century. New chapters by 36 contributors illustrated with over 140 black-and-white images are assembled in six parts concerning both real and virtual spaces: design, materiality, alterity, technologies, cityscapes, and practice